Durability of composite assemblies under extreme conditions: Thermomechanical damage prediction of a double-lap bonded composite assembly subject to impact and high temperature. (1st April 2019) - Rizk, Georgio; Nahas, Roula; Khalil, Khaled; Challita, Georges; Legrand, Vincent; Casari, Pascal; Jacquemin, Frédéric
Abstract: The objective of this study is to simulate and predict the thermomechanical damage of composite material assemblies subjected to impact load while in a high temperature environment. Three-dimensional models were developed for a glass-fiber reinforced vinyl ester double-lap bonded composite assembly subject to combined mechanical and high thermal loads. Both thermal and mechanical models were implemented in the finite element analysis software Abaqus, using sequential heat transfer and dynamic implicit simulations. The thermal model is customized to properly simulate the thermal behavior of composites and generate accurate results while the mechanical model uses the existing functions of Abaqus. For a double-lap composite assembly, thermomechanical failure is predicted in the adhesive zone, at the adherent/adhesive interface, as the adhesive deteriorates at the early stages of exposure. The adherent also deteriorates but at a slower rate. Furthermore, stress concentration is observed at the edges of the stress distribution along the adhesive length, while the average stress along the length decreases gradually as a function of the fire exposure time. The conducted simulations made it possible to predict the stress distribution field variation as a function of time in the double-lap bonded assembly under a combined thermal-impact load. This would serve as a valuable tool for composite structure designers in sizing bonded composite assemblies for their structural projects, as the specifications for certain structures impose a time of evacuation of the structure during a shock and triggering of a fire.